TEACHERS' PERSPECTIVE TOWARDS POST-METHOD PEDAGOGY - Muhammad Anjar Nugraha (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2018)
Post-method pedagogy offers with the controversial claim that in the 21st era the play of teaching method is dying. Post-method pedagogy is the current issue of English Language Teaching (ELT) nowadays. This is a qualitative case study aimed to seek English teachers’ perspective towards post-method pedagogy. Ten English teachers from different school grade were asked to answer the questionnaire and semi-structured interview, which is related to what method usually do in their classroom, and do they have positive attitudes towards post-method pedagogy or vice versa. Results suggested that, although the teachers did not spell out exactly what post-method is, they have a positive response on the post-method pedagogy parameter dimension and frameworks had stated. It is recommended to the further research to do with the wider scale in order to get the wider perception towards the 21st current issue of ELT.